Examining cognitive and metacognitive predictors of self-efficacy and motivation of undergraduate students at a research-intensive university in the UAE - Mejri, Sami B; Muhammad, Abdussabur; Alabdulrazzaq, Hala (Journal of International Students, 2026)
The Motivated Strategies for Learning Questionnaire (MSLQ) was used. This study examined the relationships among the cognitive, metacognitive, and affective domains, their predictive value for self-efficacy, and their impact on academic motivation and performance among 363 students at Khalifa University. The results revealed a strong positive correlation between self-efficacy and motivation (r (361) = .893, p < .001) and a moderate positive correlation between cognitive strategy use and motivation (r (361) = .515, p < .001), highlighting the importance of cognitive engagement and self-belief in academic success. Regression analyses revealed that affective strategies, such as emotional regulation and anxiety management, had a small but significant effect on self-efficacy, F (1, 361) = 3.97, p = .047). Demographic variables, including GPA and academic standing, accounted for approximately 10% of the variance in self-efficacy, with GPA as the strongest predictor.